From Hollywood to the Home Movie: Reclaiming the Image of Asian Americans and Pacific Islanders in Film, 1894–1945 - Lu, Megan (Cahiers d'histoire, 2023)
The American film industry has a long and sustained history of silencing Asian Americans and Pacific Islanders (AAPIs). This paper explores early Hollywood’s (pre-1950) erasure of these communities. It maps how popular narrative devices, such as the yellow peril, reflected contemporaneous bigotry and how institutional practices, such as yellowface, severely limited participation in the industry. Simultaneously, it explores how contemporaneous amateur filmmaking, including Dave Tatsuno’s footage during his incarceration in the Topaz War Relocation Center, complicates these narratives. Amateur filmmaking as a medium of self-representation provided AAPIs the opportunity to reclaim their image and reassert their voice.